Global, regional, and national burdens of osteoarthritis from 1990 to 2021: findings from the 2021 global burden of disease study - Li, Han-Zheng; Liang, Xue-Zhen; Sun, Yi-Qing; Jia, Hai-Feng; Li, Jia-Cheng; Li, Gang (Frontiers in Medicine, 2024)
Osteoarthritis (OA) is a common chronic degenerative joint disease and a major contributor to disability and elevated morbidity rates worldwide. This study assesses the epidemiological trends of OA from 1990 to 2021, analyzing data by sex, affected joint sites, and Socio-Demographic Index (SDI) across global, regional, and national levels.Data on OA were obtained from the (Global Burden of Disease Study) 2021. The age-standardized rates (ASR) for OA were computed, and the estimated annual percentage changes (EAPC) in ASR were determined to evaluate trends in incidence and disability-adjusted life years (DALYs) over the past three decades. Pearson's correlation analysis was conducted to explore the relationship between ASR and the Socio-Demographic Index (SDI). Additionally, Joinpoint regression software and age-period-cohort (APC) analysis were applied for a comprehensive examination of the OA data.From 1990 to 2021, the global burden of OA has markedly increased. In 2021, there were approximately 466.3 million new OA cases, with an ASR of incidence(ASIR) of around 535 per 100,000 population. The prevalence of OA reached about 606.9 million cases, and DALYs rose to approximately 213 million.The burden of OA is significantly higher in women compared to men, as reflected by higher ASR of incidence, prevalence, and DALYs associated with OA.In 2021, the ASR of incidence was positively associated with the SDI regions.Globally, knee osteoarthritis (KOA) remains the most common form of OA. Among the various risk factors, high body mass index (BMI) emerged as the most critical contributor to OA.From 1990 to 2021, the global burden of OA has steadily increased,leading to a significant decline in health and overall quality of life.The global prevalence of OA indicates higher incidence rates among women and in countries with a higher SDI.Governments and policy makers globally must prioritize increasing awareness of the risk factors and consequences related to OA,promote early diagnostic and therapeutic services, and implement targeted interventions to mitigate the growing burden of OA.